2013
DOI: 10.14773/cst.2013.12.4.171
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion characteristics and interfacial contact resistances of TiN and CrN coatings deposited by PVD on 316L stainless steel for polymer electrolyte membrane fuel cell bipolar plates

Abstract: In a polymer membrane fuel cell stack, the bipolar plate is a key element because it accounts for over 50% of total costs of the stack. In order to lower the cost of bipolar plates, 316L stainless steels coated with nitrides such as TiN and CrN by physical vapor deposition were investigated as alternative materials for the replacement of traditional brittle graphite bipolar-plates. For this purpose, interfacial contact resistances were measured and electrochemical corrosion tests were conducted. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In general, when TiN is deposited by PVD and CVD methods, pores form on the surface, which can contribute to corrosion. 27) In the case of ion nitriding, pore formation differs, depending on the gas, time, and temperature used in the nitriding process. 28,29) In the present study, no pores formed, and no corrosion-related damage was observed.…”
Section: Electrochemical Experimentsmentioning
confidence: 99%
“…In general, when TiN is deposited by PVD and CVD methods, pores form on the surface, which can contribute to corrosion. 27) In the case of ion nitriding, pore formation differs, depending on the gas, time, and temperature used in the nitriding process. 28,29) In the present study, no pores formed, and no corrosion-related damage was observed.…”
Section: Electrochemical Experimentsmentioning
confidence: 99%